IMPLEMENTASI KAIDAH-KAIDAH ISLAM DALAM PENGELOLAAN ZAKAT PROFESI - SUTARDI SUTARDI; MUHAMMAD IRWAN; IHSAN RO’IS (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2017)
The theme of the article is the banks and financial institutions. This study aims to determine the implementation of Islamic rules in the management of "zakat profesi". Management views of managers understanding of the principles of Islam. The research is qualitative descriptive. Data collection using interviews, observation, and documentation. Resource is the management and participants "Program Peduli Dhuafa". The results showed the “zakat profesi” management has implemented the rules of Islam. In executing the management has implemented four properties ie Muhammad SAW: siddiq, amanah, tabligh and fathonah.